Serum soluble CD25 as a risk factor of renal impairment in systemic lupus erythematosus — a prospective cohort study. (June 2018) - Zhang, R J; Zhang, X; Chen, J; Shao, M; Yang, Y; Balaubramaniam, B; Sun, X L; Ambrus, J L; He, J; Li, Z G
Objective: Serum soluble CD25 (sCD25) could be used as a biomarker for disease activity in conditions associated with T-cell activation including various autoimmune diseases. This study aimed to explore the role of sCD25 as an indicator of disease activity and organ involvement in patients with systemic lupus erythematosus (SLE). Methods: Serum samples were collected from 107 SLE patients and 92 age-matched healthy controls (HCs). All patients were followed up for 24 weeks, and sCD25 was measured by enzyme-linked immunosorbent assay. Clinical and laboratory data were recorded at baseline and then every two weeks until week 24. The Systemic Lupus Erythematosus Disease Activity Index-2000 (SLEDAI)-2K was adopted for assessing disease activity at all visits. Results: Serum sCD25 levels were significantly increased in SLE patients compared to those in HCs ( p  < 0.001). More patients in the high-sCD25 group had lupus nephritis, arthritis and vasculitis ( p  = 0.010, p  = 0.023 and p  = 0.042, respectively). SLEDAI-2K, erythrocyte sedimentation rate, C-reactive protein and 24-hour urinary protein excretion were all associated with high levels of sCD25 ( p  < 0.001, p  = 0.002, p  = 0.038 and p  = 0.029, respectively). During the 24-week follow-up, more patients in the high-sCD25 group developed renal impairment (48% vs 6.2%, p  = 0.005), and higher levels of sCD25 ( p  = 0.033) were found at the time of onset of renal disease. Conclusions: Serum sCD25 is a hallmark of disease activity and a predictor of renal disease in patients with SLE.